Knowledge and data: Achieving food and nutrition security through open access - Yerramareddy, Indira; Babu, Suresh Chandra (International Food Policy Research Institute, 2018)
Despite global reductions in hunger, malnutrition, and poverty, food and nutrition insecurity remain a global challenge. Reducing hunger and malnutrition requires evidence-based decision making, which in turn depends upon access to knowledge and data. Support is growing for “open data”—data that can be freely used, shared, and built on by anyone, anywhere, for any purpose. Widespread open access to useable knowledge and data for farmers, businesses, and governments can improve the performance of food systems. However, under increasing isolationism and nationalism, there are worrisome restrictions on the free flow of knowledge and data. Ensuring open access will be critical to supporting better food systems and strengthening food and nutrition security.